A review of research on culturally adapted cognitive behavioral therapy (CA-CBT) - Yizhou Zhang (Advances in Social Behavior Research, 2026)
Cognitive behavioral therapy (CBT) is a short-term, highly effective, evidence-based treatment recommended by numerous national organizations; however, because it is rooted in Western cultural values, its direct application to non-Western cultural groups may result in reduced efficacy and high dropout rates. Consequently, culturally adapted cognitive behavioral therapy (CA-CBT) has emerged. This paper conducted a systematic review of empirical studies, randomized controlled trials, and meta-analyses on CA-CBT published between 2010 and 2024 in databases such as Web of Science, PubMed, and PsycINFO, examining the conceptual evolution, evidence base, key therapeutic elements, and treatment sustainability of this approach. The results indicated that CA-CBT, while retaining the core theoretical framework of CBT, significantly improved outcomes for common psychological conditions, such as depression, anxiety, post-traumatic stress disorder, and postpartum depression, among other mental health conditions. The therapeutic effects persisted during follow-up, and the dropout rate was significantly lower than that of standard CBT. The conclusion states that CA-CBT serves as an effective bridge connecting Western evidence-based treatment with local cultural practices, and its success lies in respecting and skillfully integrating the patient's cultural background. Future research should standardize efficacy assessment criteria, expand evidence from cognitive neuroscience, and focus on eliminating financial and geographic barriers to treatment access for patients.